Integrating flood management and agri-environment through washland creation in the UK. - Morris, Joe; Bailey, A. P.; Alsop, D.; Vivash, R. M.; Lawson, C. S.; Leeds-Harrison, Peter B. (Cranfield University, 2004)
In many river floodplains in the UK there has been a long history of flood defence, land reclamation and water regime management for farming. In recent years, changing policies with respect to farming, environment and flood management are encouraging a re-appraisal of land use in rural areas. In particular, there is scope to develop, through the use of appropriate promotional mechanisms, washland areas which will simultaneously accommodate winter inundation, support extensive farming methods, deliver environmental benefits, and do this in a way which can underpin the rural economy. This paper explores the feasibility of flood storage and washland creation, the likely economic impacts (on the agricultural sector) of this type of development, and the financial and institutional mechanisms required to achieve implementation. The outcome is the identification and assessment of a washland package within the UK agri-environment framework. However, given the diversity of circumstance and practice, it is suggested that a range of options, and not just those associated with management agreements and annual payments, is used for the management and administration of washland areas.